mathematical model for segmentation of the overall planning of puplic redemption company- ministry of industry and minerals - بخيت, عبدالجبار خضر; عباس, وعود سالم (Journal of Economics and Administrative Sciences, 2016)
AbstractThe study presents a mathematical model with a disaggregating approach to the problem of production planning of a fida Company; which belongs to the ministry of Industry. The study considers disaggregating the entire production into 3 productive families of (hydraulic cylinders, Aldblatt (dampers), connections hydraulics with each holds similar characteristics in terms of the installation cost, production time and stock cost. The Consequences are an ultimate use of the available production capacity as well as meeting the requirements of these families at a minimal cost using linear programming. Moreover, the study considers developing a Master production schedule that drives detailed material and production requirements from sub-schedules available on the productive families after they have been disaggregated into their main products. The schedule adopts a short range planning horizon of typically one week. It is important plan production with less defective products within each productive family line Therefore, a mathematical model using mixed integers linear programming approach has proved its usefulness in reducing defects, cost as well as meeting deadlines. Finally, we present in this study a practical instance of the a implication of this model on Al- fida company, which reduced the total production cost from(361,407,800) to (390,330,100) in 2014 with a saving of (28, 922, 300) . The above implication and others proves the importance of using mixed integers linear programming model with disaggregating approach in production planning processes.